Botanical Origin of Pesticide Residues in Pollen Loads Collected by Honeybees During and After Apple Bloom - Favaro, Riccardo; Bauer, Lisbeth Marie; Rossi, Michele; D’Ambrosio, Luca; Bucher, Edith; Angeli, Sergio (Frontiers in Physiology, 2019)
Honeybees closely rely on insect-pollinated plants for their survival. Each forager bee displays a tendency of loyalty toward specific plant species during the many daily foraging flights. Therefore, a single pollen load is mostly composed of only one botanical species. Due to the ease of collection, pollen loads have been extensively used as a proxy for the detection of pesticide residues. Pollen is the main protein food source for colonies, and its contamination has also been addressed as a reason for the colony losses phenomenon of the last decades. As honeybees fly over a variable but wide range territory, they might collect pollen from both agricultural, urban and wild environments, also displaying considerable preferences in botanical sources between colonies of the same apiary. It is thus difficult to address the source of the pesticide contamination, when pollen is analysed as a whole. In the current study, a practical and reliable approach has been proposed to narrow down the source of contamination. Pollen loads have been collected from colonies placed in 8 locations over large apple orchard extensions in Trentino-South Tyrol region (Italy), during and two weeks after apple blossom. The pollen loads have been separated by the colour due to the predominant plant species. On each colour group, palynology and multi-residual chemical analyses have been performed in parallel. The pollen hazard quotient (PHQ) has been used to estimate the risk to honeybees of each colour group and of the total collected pollen. The frequency and the amount of pesticide residues differed according to the collection periods, the locations and the pollen colour groups. Pesticide variations have been confirmed among pollen groups of the same location, proving the validity of this approach. Although differences among locations did not allow to identify a unique source of contamination, it seems that the pollen from plants outside the agricultural areas has as much residues as the pollen from apple orchards.